“La sfera e la croce”, ovvero i feti abortiti come rifiuto da distruggere o come resti mortali da onorare (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. L’art. 7 del d.p.r. n. 285 del 1990 - 2. Parti anatomiche amputate e rifiuti infettivi - 3. Riflessioni sul trattamento dei feti abortiti - 4. Qualche precisazione su temi connessi - 5. A mo’ di conclusione.“The Ball and the Cross”: the fetuses aborted as medical waste to be destroyed or as mortal remains to be honouredABSTRACT: Is there an obligation for Italian hospitals to destroy aborted fetuses as infectious waste? Yes, for a recently published paper. On the contrary, we’ll se that, even without an explicit application of the mother, the hospital has the right not to destroy the aborted fetus, proceeding to its burial or cremation. In fact, it is necessary to interpret correctly the article 7 of the Decree of the President of the Republic n. 285 of 1990, also applying the rules on the treatment of medical waste. So it will be clear that the same regulations for the treatment of recognizable body parts must be applied to the treatment of aborted fetuses.